2013
DOI: 10.1111/asj.12042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the feeding sequence of concentrate and forage and the feeding ratio of sake cake to grass hay on the characteristics and the entrapment effect of the ruminal mat in non‐lactating dairy cows

Abstract: The effects of the feeding sequence of concentrate and forage, and of the feeding ratio of sake cake (SC) to grass hay (GH) on the ruminal mat characteristics and the entrapment effect for steamed flaked corn (SFC) by the mat were evaluated. Three non-lactating, rumen-cannulated Holstein cows were offered SC and GH using a ratio of 35:65 (SC35) or 65:35 (SC65). For SC35, SFC was fed at 1 h after or immediately before offering SC and GH, while for SC65, SFC was only fed at 1 h after. To estimate the degree of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although this difference is an error in the design of the experiment, it could be judged that the effects of KP fiber on the results were significant even without this difference. Izumi (2013) showed that even if NFFSs constituted a large component of the diet, the ruminal mat was formed when grasses were used as supplementary forage sources. Fiber particles of most grasses are inherently long and buoyant and get easily tangled, whereas legume particles are short and chunky and have high specific gravity, which facilitates their passage through the rumen (Wilson & Kennedy, 1996).…”
Section: Ruminal Mat Formation and Rumen Fillmentioning
confidence: 99%
“…Although this difference is an error in the design of the experiment, it could be judged that the effects of KP fiber on the results were significant even without this difference. Izumi (2013) showed that even if NFFSs constituted a large component of the diet, the ruminal mat was formed when grasses were used as supplementary forage sources. Fiber particles of most grasses are inherently long and buoyant and get easily tangled, whereas legume particles are short and chunky and have high specific gravity, which facilitates their passage through the rumen (Wilson & Kennedy, 1996).…”
Section: Ruminal Mat Formation and Rumen Fillmentioning
confidence: 99%